1998
DOI: 10.1038/sj.bmt.1701126
|View full text |Cite
|
Sign up to set email alerts
|

Fatal CMV pneumonia associated with steroid therapy after autologous transplantation in patients previously treated with fludarabine

Abstract: Summary:Fludarabine has been associated with an increased risk of opportunistic infections, possibly related to the induction of profound CD4 ϩ lymphopenia. We observed two cases of cytomegalovirus pneumonia (CMV-IP) in a total of nine patients over a 5-year period who had previously received fludarabine and who proceeded to autografting. Both patients also received steroids posttransplant. CMV-IP was observed in one of 104 other autograft recipients over this time who had not received prior fludarabine. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…11 Failure of pentamidine aerosol as PCP prophylaxis in APBSCT recipients has been reported. 2,12 Our case also suggests that pentamidine inhalation may not be adequate for PCP prophylaxis in APBSCT, especially in patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…11 Failure of pentamidine aerosol as PCP prophylaxis in APBSCT recipients has been reported. 2,12 Our case also suggests that pentamidine inhalation may not be adequate for PCP prophylaxis in APBSCT, especially in patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 94%
“…In one study, CMV seropositivity prior to transplant, viruria and viremia were shown by a multivariate analysis to be significant risk factors for CMV pneu-monia following ABMT. 5 Grigg et al 12 recently reported two patients with CMV pneumonia, who had received fludarabine prior to transplant and corticosteroids after transplant. They speculated that the combination of fludarabine and corticosteroids may have increased the risk of CMV pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations